2017
DOI: 10.1038/pr.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-related microRNAs in maternal breast milk are influenced by premature delivery

Abstract: Background Maternal breast milk (MBM) is enriched in microRNAs, factors that regulate protein translation throughout the human body. MBM from mothers of term and preterm infants differ in nutrient, hormone, and bioactive factor composition, but the microRNA differences between these groups have not been compared. We hypothesized that gestational age at delivery influences microRNA in MBM, particularly microRNAs involved in immunologic and metabolic regulation. Methods MBM from mothers of premature infants (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 38 publications
1
99
1
4
Order By: Relevance
“…Zhou et al also noted immune related miRNAs were rich in breast milk exosomes. As mentioned previously, the microRNA profile differs between full-term and preterm breast milk [128]. Carney et al also noted that the gene targets of the nine microRNAs that differed between both groups influenced metabolic processes such as lipid metabolism.…”
Section: Micrornamentioning
confidence: 82%
See 1 more Smart Citation
“…Zhou et al also noted immune related miRNAs were rich in breast milk exosomes. As mentioned previously, the microRNA profile differs between full-term and preterm breast milk [128]. Carney et al also noted that the gene targets of the nine microRNAs that differed between both groups influenced metabolic processes such as lipid metabolism.…”
Section: Micrornamentioning
confidence: 82%
“…The microRNA profile of human milk has also been compared between mothers of full-term versus mothers of preterm infants. A study by Carney et al identified differences in the expression profiles of nine miRNAs in the skim milk and lipid fractions of preterm breast milk when compared to full-term samples [128]. Furthermore, a recent investigation by Shiff et al noted that miRNA-320 was expressed less in preterm milk while miRNA-148 was more expressed when compared to full-term milk [129].…”
Section: Micrornamentioning
confidence: 99%
“…Finally, a recent study on milk microRNAs profiles during premature delivery was not able to validate microRNAs as candidates for early diagnosis of this condition (Carney et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…In milk, microRNA expression was related to mammary gland conditions, including infections (Iannaccone et al., ; Lai et al., , ; Sun et al., ), cancer (Decmann et al., ; Do Canto et al., ; Hesari et al., ), pregnancy and lactation status (Carney et al., ; Perri et al., ; Schanzenbach et al., ), and maternal diet (Chen et al., ). Therefore microRNAs in milk were studied for their potential as biomarkers (Gustafson, Tyryshkin, & Renwick, ; Melnik & Schmitz, ) such as quality controls of commercial milk (Oh et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation